"Track style" children's fundamental movement skills test: construction and verification of an efficient evaluation system - Yubo Wang; Shuang Liang; Baofeng Zhang; Lingyue Meng; Yan Xiong (Frontiers Media S.A., 2024)
ObjectivesThis study aimed to develop an efficient tool for assessing children's fundamental motor skills, the "Track style" Children's Fundamental Movement Skills Test (TCFMST), based on theories of motor development integrated with Chinese cultural context and physical education teaching situations.MethodsStarting from a literature analysis, the study selected items from existing fundamental movement skill (FMS) assessments, textbooks, physical education and health standards, and children's movement guidelines to construct a pool of test items. Subsequently, the items were screened and optimized using the Delphi method. Finally, the feasibility, discrimination, difficulty, reliability, and validity of the constructed test were examined using testing methods.ResultsThe TCFMST includes three dimensions: locomotive skills, body control skills, and manipulative skills, with a total of 10 items. The difficulty and discrimination of each item are appropriate; the correlation coefficients for retest reliability range from 0.789 to 0.943 (p < 0.01). The results of exploratory factor analysis indicate that the common factors align with the hypothesized three dimensions, indicating good structural validity of the test. The concurrent validity results show a correlation coefficient of −0.510 (p < 0.01) between the TCFMST and the total score of TGMD-3, indicating a moderate correlation between the two tests.ConclusionThe TCFMST developed in this study has good difficulty, discrimination, reliability, and validity. It also features strong operability, a short duration, and high interest. It can serve as an important tool for monitoring children's fundamental motor skill levels.